Cardiac Safety in Breast Cancer Patients Receiving Pegylated Liposome Doxorubicin Sequential Anti-HER2 Monoclonal Antibody Therapy - Huang, Ping; Huang, Jia-huan; Zheng, Ya-bing; Cao, Wen-ming; Shao, Xi-ying; Chen, Jun-qing; Huang, Yuan; Li, Guang-liang; Sharma, K; Zhou, Huan-huan; Wang, Xiao-jia; Jin, Hong-chuan; et al. (Frontiers in Pharmacology, 2022)
Background: Cardiotoxicity associated with sequential use of anthracyclines followed by trastuzumab is quite common in the adjuvant therapy of patients with HER2-positive early breast cancer (eBC). However, the cardiac safety of trastuzumab concurrent with pegylated liposomal doxorubicin (PLD) is less revealed. Method: We retrospectively collected the clinical data in patients with HER2-positive eBC treated with PLD and cyclophosphamide (PLD-C) followed by taxanes plus trastuzumab ±pertuzumab (TH or TPH) and then finished standard anti-HER2 treatment for a total of 12 months from June 2012 to August 2021. The primary endpoints were clinical cardiotoxicity and sub-clinical cardiotoxicity. Result: 70 eligible patients were enrolled. Among them, 55 (78.6%) patients received PLD-C →TH and 15 (21.4%) patients received PLD-C→ TPH. The median follow-up time was 41.8 months. Until August 2021, only 2 patients had recurrent or metastatic diseases with the 2-year and 5-year disease-free survival (DFS) of 98.6% and 96.8%, respectively. Clinical cardiotoxicity occurred in 6 (8.6%) patients, and all of them had absolute decline of ≥16% from baseline left ventricular ejection fraction (LVEF), but never to below the lower limit of normal (LLN=50%). Subclinical cardiotoxicity events occurred in 17 (24.3%) patients, and all of them had absolute declines of ≥10% and <16% from baseline LVEF, but never to below the LLN. No patients were interrupted from treatment, and all patients completed anti-HER2 treatment for 12 months. The sharpest decrease in LVEF was observed at 18th months after the start of PLD treatment. The cumulative incidences of cardiac toxicity in clinical and subclinical were 9.8% and 28.3%, respectively. In univariate analysis, body mass index (BMI), age, left chest wall radiotherapy and ongoing cardiovascular risk factors were not significantly associated with clinical or subclinical cardiotoxicity (P>0.05). No patients had congestive heart failure (CHF) or death caused by PLD or anti-HER2 drugs. Conclusion: Sequential use of PLD and trastuzumab showed lower incidence of clinical cardiotoxicity presented as asymptomatic decreased LVEF, compared with previous clinical studies containing conventional anthracycline, taxanes and trastuzumab. The study regimen demonstrated good cardiac tolerance and is an alternative strategy for cardio-protection in patients with HER2-positive eBC.